2001
DOI: 10.4049/jimmunol.166.7.4422
|View full text |Cite
|
Sign up to set email alerts
|

The NK Cell MHC Class I Receptor Ly49A Detects Mutations on H-2Dd Inside and Outside of the Peptide Binding Groove

Abstract: N atural killer cells are a group of lymphocytes that spontaneously lyse certain tumor targets (1). The finding that cell lines defective for MHC class I expression were efficiently lysed by NK cells led to the missing self hypothesis: NK cells kill cells that lack normal expression of MHC class I molecules (2). Recent studies have established that NK cells express inhibitory receptors for MHC class I molecules (3, 4). The receptors can be classified into two groups by their structural characteristics. One gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
(64 reference statements)
2
27
0
Order By: Relevance
“…The unique orientation of Ly49C on H-2K b seemed to be due to a different mode of dimerization for Ly49C compared with Ly49A. In the Ly49C cocrystal, the Ly49C dimer was more open, allowing one Ly49C receptor to symmetrically bind two H-2K b molecules simultaneously, whereas in the Ly49A cocrystal, Ly49A dimerization was more closed, resulting in an asymmetrical binding orientation on a single H-2D d molecule (25,26). Ly49A has since been seen to assume a similar open dimerization state, according to nuclear magnetic resonance solution studies, capable of binding two H-2D d molecules simultaneously (44), making variable Ly49 dimerization states unlikely mediators of allele specificity.…”
Section: Ly49g Recognition Of H-2d D Is Disrupted By Mutagenesis Of Smentioning
confidence: 96%
See 1 more Smart Citation
“…The unique orientation of Ly49C on H-2K b seemed to be due to a different mode of dimerization for Ly49C compared with Ly49A. In the Ly49C cocrystal, the Ly49C dimer was more open, allowing one Ly49C receptor to symmetrically bind two H-2K b molecules simultaneously, whereas in the Ly49A cocrystal, Ly49A dimerization was more closed, resulting in an asymmetrical binding orientation on a single H-2D d molecule (25,26). Ly49A has since been seen to assume a similar open dimerization state, according to nuclear magnetic resonance solution studies, capable of binding two H-2D d molecules simultaneously (44), making variable Ly49 dimerization states unlikely mediators of allele specificity.…”
Section: Ly49g Recognition Of H-2d D Is Disrupted By Mutagenesis Of Smentioning
confidence: 96%
“…Through mutagenesis studies and examination of KIR/MHC I cocrystal structures, it has been demonstrated that KIR bind MHC I on the top surfaces of the ␣1 and ␣2 helices of MHC I, and this principally involves interaction of polymorphic KIR residues with HLA-C residues 77 and 80 (21,22). The molecular interaction between mouse Ly49 and MHC I has also been studied by mutagenesis (23)(24)(25)(26)(27)(28)(29) and examination of cocrystal structures of Ly49A/H-2D d and Ly49C/H-2K b (30,31), and occurs primarily at a large interface known as site 2 that encompasses MHC I residues below the peptide-binding groove, within the ␣3 domain, and on the ␤ 2 -microglobulin (␤ 2 m). What has remained poorly understood is the mechanism by which this site 2 interface, which is highly conserved both within and between rat and mouse MHC I alleles, can engender the observed allele specificity of Ly49 receptors.…”
mentioning
confidence: 99%
“…Crystallographic studies revealed two potential interaction sites on MHC class I at which interactions with Ly49 receptors might take place: Site 1 is on the left side of the peptide-binding cleft (when viewed from above with the α1 helix shown on top); site 2 is below the peptide-binding cleft (14). Mutational studies demonstrated that the Ly49 receptors engage site 2 in trans to inhibit effector functions, because point mutations at site 2 abrogated the capacity of transfected MHC class I molecules to inhibit NK cells in an Ly49-dependent manner (15)(16)(17). Furthermore, we recently showed that these same residues are involved in conferring Ly49-dependent licensing effects because transgenic (Tg) expression of site 2-mutant MHC class I molecules failed to induce licensed NK cells, whereas wild-type MHC class I alleles allowed licensing (18).…”
Section: Significancementioning
confidence: 99%
“…Three of the peptides used in this context (Refs. 25 d reduce binding to Ly-49A (57), whereas single mutations of residues 104 and 107 did not affect the interaction with Ly-49A (33,58). The Ly-49C mutation K225N/ I226T that showed reduced MHC class I binding is close to this loop when Ly-49C is modeled onto the Ly-49A-H-2D d co-crystal.…”
Section: Discussionmentioning
confidence: 99%